Microeconomic Determinants of Underemployment and Unemployment in Ecuador 2019–2022 - Linthon-Delgado, Diego; Méndez-Heras, Lizethe; Venegas-Martínez, Francisco (International Journal of Economics and Financial Issues, 2024)
The aim of this paper is to identify the microeconomic determinants of underemployment and unemployment in Ecuador before and after COVID-19. A multinomial logit model was estimated on the accumulated data from the National Employment, Unemployment and Underemployment Survey (ENEMDU) for 2019 and 2022. The results show that the average worker has a 59% probability of being in an adequate job, 35% of being underemployed and 6% of being unemployed. These probabilities change significantly depending on the worker's education and experience. In addition, significant differences were evident by gender, ethnicity, role in the home, and marital status. These differences increased after COVID-19. Thus, underemployment and unemployment promote labor inequality in Ecuador. Based on the results, the public policy should be aimed at reducing economic and opportunity inequalities because vulnerable groups were identified in the labor market.